2018
DOI: 10.1051/matecconf/201824901002
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Dynamic Characterization of Sustainable Composites Based on Food Packaging Waste

Abstract: Composites made from food packaging waste are recently introduced to the industry as promising materials that aim to reduce the environmental waste and to develop cost effective products. They possess good physical properties, which makes them potential competitors to wood based composite structures such as commercial particleboard (PB), and medium density fiberboard (MDF). Despite the expected advantages, the mechanical and dynamic behaviour of this genuine structure still needs to be studied and tested to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Nassef et al [37] reported in 2018 that composites made from 100% aseptic cartons (target density of 0.8 g cm −3 and a thickness of 10 mm) and a skin of woven glass fiber fabric possessed higher dynamic characteristics in terms of damping ratio compared to commercial particleboard and medium density fiberboard. Bending tests showed competitive MOR values of both composites, with the addition of glass fiber fabric enhancing the MOR values.…”
Section: Blendsmentioning
confidence: 99%
“…Nassef et al [37] reported in 2018 that composites made from 100% aseptic cartons (target density of 0.8 g cm −3 and a thickness of 10 mm) and a skin of woven glass fiber fabric possessed higher dynamic characteristics in terms of damping ratio compared to commercial particleboard and medium density fiberboard. Bending tests showed competitive MOR values of both composites, with the addition of glass fiber fabric enhancing the MOR values.…”
Section: Blendsmentioning
confidence: 99%
“…Valente et al (2011) investigated some of the mechanical properties of hybrid thermoplastic composites made from wood flour and recycled glass fibers. Some researchers evaluated the properties of different types of polymer-based composites produced with TPBs (Avella et al 2009;Sanchez-Cadena et al 2013;Yilgor et al 2014;Bekhta et al 2016;Nassef et al 2018;Aranda-García et al 2020;Gallego et al 2020;Sujatha et al 2021;Guillén-Mallette et al 2021). Kaymakçı et al (2012) and Ayrılmış et al (2013) evaluated some of the mechanical properties of a WPC produced with TPBs and rice husk flour.…”
Section: Introductionmentioning
confidence: 99%
“…Wood-based materials and their composites are used in an increasing number of industries. First of all, they have been used in the furniture (Mirski et al 2017), packaging (Nassef et al 2018;Palka and Tutak 2018), and construction industries (Heidari et al 2019), in which they constitute the low-emission construction sector (Hildebrandt et al 2017). Wood-based materials consist mainly of wood chips and dust covered with, for example, PVC laminates (Narlıoğlu et al 2018), laminated with thermally compressed veneer (Buyuksari 2012), décor paper, and resin/impregnated décor papers (Istek et al 2010) or coated with veneers and continuous press laminates (Nemli and Çolakoǧlu 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the composition of wood-based materials is enriched due to the situation related to the problems of wood scarcity and forest protection. Thanks to it, techniques for implementing winter rape (Gajdačová et al 2018) or food packaging waste (Nassef et al 2018) for the production of wood-based materials are being developed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation